2016
DOI: 10.1097/mao.0000000000001066
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Hearing Preservation Outcomes After Cochlear Implantation for Electric-Acoustic Stimulation

Abstract: Long-term HP is feasible in a subset of patients. Patients with sufficient long-term residual hearing had the prerequisite to benefit from additional acoustic stimulation. No correlation of total hearing loss with etiology, electrode design, or surgical approach was evident. Apart from individual effects of structural damage or inflammation, genetic factors are suggested to influence HP. Cases with total hearing loss still demonstrated successful speech perception in long-term monosyllable recognition scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 30 publications
9
63
1
1
Order By: Relevance
“…For recipients of L24 arrays, the proportion of individuals experiencing delayed hearing loss versus stable hearing was not significantly different according to insertion approach, which is consistent with a one-year follow-up study by Adunka and colleagues (2014). In a more recent report, Helbig and colleagues (2016) compared insertion approaches for long-term hearing preservation rates (up to 5 years). A higher proportion of individuals undergoing round window insertions tended to show partial hearing loss immediately follow surgery.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…For recipients of L24 arrays, the proportion of individuals experiencing delayed hearing loss versus stable hearing was not significantly different according to insertion approach, which is consistent with a one-year follow-up study by Adunka and colleagues (2014). In a more recent report, Helbig and colleagues (2016) compared insertion approaches for long-term hearing preservation rates (up to 5 years). A higher proportion of individuals undergoing round window insertions tended to show partial hearing loss immediately follow surgery.…”
Section: Discussionsupporting
confidence: 75%
“…Gstoettner et al 2006; Santa Maria et al 2013; Lenarz et al 2013; Adunka et al 2014; Helbig et al 2016; van Abel et al 2015; Roland et al 2016; Gantz et al 2016), and that is true for the sample included in the present study as well. Approximately 80% of individuals in the present study had hearing thresholds better than 90 dB HL and were using acoustic amplification in combination with electrical stimulation at the conclusion of the study.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Ultimately 21% of patients completely lost all low-frequency hearing. 77 As expected, they found that hearing preservation was dependent on electrode array design and surgical approach. They found that patients who lost all low-frequency hearing performed more poorly and they also suggested that these patients be considered for reimplantation with a full-length electrode given prior evidence of the utility of this approach.…”
Section: Hearing Preservation In Cochlear Implantation: Surgical Techsupporting
confidence: 53%
“…79 They found that long-term hearing stabilized with a decline per year consistent with previous studies around 1 dB per year. 77,80 More recent updated results with the L24 electrode array alone demonstrated similar preservation rates at 5 years, with 94% preserving some degree of low-frequency hearing but only 72% using the EAS component of the system. 81 Similarly, Pillsbury et al demonstrated hearing preservation using the MED-EL EAS system, reporting that 79% of patients experienced less than 30 dB change in low-frequency hearing, but they reported a much higher continued use of the EAS system at 97% of patients at 1 year follow-up.…”
Section: Hearing Preservation In Cochlear Implantation: Surgical Techmentioning
confidence: 92%